To find the values of x that make the equation equal zero, we need to solve for x when the equation is set equal to zero:
(x - 3)(x + 5) = 0
This equation will be equal to zero if either (x - 3) or (x + 5) is equal to zero. Setting each of them equal to zero and solving for x, we have:
x - 3 = 0 or x + 5 = 0
Solving the first equation:
x - 3 = 0
x = 3
Solving the second equation:
x + 5 = 0
x = -5
Therefore, the values of x that make the equation equal to zero are x = 3 and x = -5.
Find the values of x that make the following equation equal zero:
(x-3) (x+5)=0
1 answer